2018
DOI: 10.1088/1555-6611/aae058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an undoped-InGaN waveguide on the optical confinement and carrier dynamics of InGaN laser diodes

Abstract: In this paper, we have analyzed the performance of laser diodes (LDs) with an undoped In x Ga 1−x N waveguide in association with variable In mole fractions varying from 0% to 6%. The InGaN waveguide significantly affected optical confinement and carrier dynamics in the LD. Laser output power, internal quantum efficiency (IQE), quantum well (QW) gain and optical confinement factor (OCF) are analyzed in correlation with In content in the waveguide. The OCF for TE1 mode at x = 0 is 0.0079, and it increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although, the random structures are easy to fabricate and design with minimum infrastructure requirement, they are complex to reproduce and rescale for the industry required bulk production, it is better to look for the periodic structures for designing LMS. Periodic nanophotonic structures (PNS) having subwavelength dimensions have been utilized and demonstrated their effectiveness successfully for a variety of optoelectronic applications [27][28][29][30][31]. PNS have a lot to offer for the design of optoelectronic devices as they have various unique advantages especially for the OSEH applications.…”
Section: Periodic Nanophotonic Structures For Light Trappingmentioning
confidence: 99%
“…Although, the random structures are easy to fabricate and design with minimum infrastructure requirement, they are complex to reproduce and rescale for the industry required bulk production, it is better to look for the periodic structures for designing LMS. Periodic nanophotonic structures (PNS) having subwavelength dimensions have been utilized and demonstrated their effectiveness successfully for a variety of optoelectronic applications [27][28][29][30][31]. PNS have a lot to offer for the design of optoelectronic devices as they have various unique advantages especially for the OSEH applications.…”
Section: Periodic Nanophotonic Structures For Light Trappingmentioning
confidence: 99%
“…Further, the optical modal field confinement factors in the active region of LD are calculated for each mode. The ordinary and extraordinary refractive index components of material layers are calculated with the frequencydependent parametric approximation [28][29][30]. The Si and Mg have the ionization energies of 13 meV and 170 meV, respectively in GaN.…”
Section: Device Modelling and Simulationmentioning
confidence: 99%
“…Xia et al have reported that the choice of Al content in the EBL is critical in optimizing the performance of the LEDs [14]. Band bending of the EBL layer also impedes the flow of hole carriers to the active region [15].…”
Section: Effects Of Electron Blocking Layer Configuration On the Dyna...mentioning
confidence: 99%
“…Lowering the In content in the waveguide and barrier region lowers the optical field confinement in the active region. The material gain increases with the reduced In content in the waveguide and barrier region but the total modal gain reduces, thus the total output power is lower as compared to the InGaN waveguide LD [25]. The optimum In content in the waveguide and barrier region is necessary, providing sufficient material gain along with the enhanced optical field confinement in the waveguide region to improve the modal gain of the LD.…”
Section: Effect Of In Content In Waveguidementioning
confidence: 99%